The Effect of Direct-to-Plant Styrene-Butadiene-Styrene Block Copolymer Components on Bitumen Modification - Zhang, Wengang (Polymers (Basel), 2019)
Five types of material, styrene-butadiene-styrene block copolymer (SBS), ethyl-vinyl-acetate (EVA), naphthenic oil, maleic anhydride grafted ethylene-vinyl acetate copolymer (EVA-g-MAH) and butylated hydroxytoluene (BHT) were used as the raw ingredients for manufacturing direct-to-plant SBS in this paper. Thirteen kinds of direct-to-plant SBS with different EVA/SBS and naphthenic oil/SBS were prepared as well as the processes diagrammatic sketch of dispersion and swelling of direct-to-plant SBS modifier in bitumen were discussed. Microscopic images of direct-to-plant SBS modified bitumen with different components were obtained using fluorescence microscopy. The micro-images were analysed and quantified with MATLAB software. The influence of key components on the micro-morphology of direct-to-plant SBS-modified bitumen is discussed, followed with the tests on melting points and the melting indexes of direct-to-plant SBS with different EVA/SBS and naphthenic oil/SBS. The performances test of bitumen and bituminous mixture modified by these direct-to-plant SBS were also conducted. Results show that, with the ratio improvement of EVA/SBS or naphthenic oil/SBS, the number of the pixel dot number of area (SBS) in microscopic images increased. Enlargement of the pixel dot number of centre line elongate and the structure fineness was observed, indicating that the dispersion and swelling effect of the SBS modifier in bitumen had been improved. Meanwhile, the macro index, such as the melting point and melting index of direct-to-plant SBS, was also improved corresponding to the increase of EVA/SBS ratio or naphthenic oil/SBS ratio. With the addition of EVA or naphthene oil content, penetration and ductility of direct-to-plant SBS modified bitumen received gradual enhancement, but the softening point and viscosity were found out to be decreased. The high-temperature and low-temperature performances of direct-to-plant SBS modified bituminous mixture can be effectively improved by adding EVA or naphthenic oil. By meeting the required performances of direct-to-plant SBS, modified bitumen and bituminous mixture, the component of direct-to-plant SBS is recommended as, SBS:EVA:naphthenic oil:EVA-g-MAH:BHT is 1:0.1–0.5:0.05–0.2:0.03:0.05. For the compatibleness of SBS with different bitumen are different, necessary tests verification is recommended to be carried out prior to usage.